STUDY OF QUALITY OF LIFE OF DENTAL PATIENTS USING IMMEDIATE PROTHESES IN THE POST-EXTRACTION PERIOD BEFORE IMPLANTATION - N.E. MITIN; E.S. PERMINOV; S.I. KALINOVSKIY; E.E. CHEKRENEVA (Avicenna Tajik State Medical University, 2019)
Objective: To investigate the quality of life (QL) of dental patients using original and classic immediate prostheses in the post-extraction tooth period before implantation. Methods: Within the frame of this study, we analyzed 86 questionnaires of patients separated into two groups: the main (n=67) and the control (n=19) group. The level of QL was assessed using the standard OHIP-14 questionnaire (Oral Health Impacts Profile) consisting of 14 questions. Patient questionnaires were conducted 4 times: to the next day after tooth extraction and overlaying of the immediate prosthesis, 2 weeks after the extraction, which corresponds to the ending of acute inflammatory phase, as well as after 3 and 6 months. In the main group, as an immediate prosthesis was used a prosthesis with an intermediate part, the basis of which is made of a hollow base with a bioinert mesh stretched between the walls of the basis of the intermediate part, and in the comparison group patients used immediate prosthesis, made by standard technology. Results: A study of the questionnaires in terms of observation from the time of tooth removal to 6 months showed that in the main and control groups on the first day after the overlaying immediate prosthesis levels of QL were 18.45±2.642 and 19.79±2.485, respectively. On the 14th day of these parameters corresponded to the values of 16.52±2.331 and 17.32±2.709. In the III and IV stages of the study (i.e. 3 and 6 months) determine the equalization of the average QL is defined by the advantage of the values in the III stage of the main group. Conclusion: The use of the original immediate prosthesis in temporary prosthetics of the post-extraction defect of the front incisor of the upper jaw gives the prevailing dynamics and more positive results relative to the standard immediate prosthesis.